PENERAPAN ELEMENT GAMIFIKASI PADA PENGEMBANGAN LAYANAN DIGITAL LIBRARY BERBASIS WEB (STUDI KASUS: MAN 2 MOJOKERTO - Dika Arissa Santoso Putri; Tri Sagirani; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2021)
MAN 2 Mojokerto Library is located at RA Basuni No. 306 Sooko, North Daleman, Japan, Kec. Sooko, Mojokerto. This library has a large collection of textbooks and non-lessons, both in print and electronic form. The library has several services including, borrowing and returns. The library wants to apply the reading culture to the community of MAN 2 Mojokerto, and wants to develop existing services in the library because the existing services are less diverse. The solution given to the problem is to develop library services into digital libraries by applying existing gamification elements such as Challange & Quest to increase the interest in reading library by answering questions from the e-book that has been read, leaderboards are used to encourage library to be diligent in reading e-books and answering as many questions as possible by displaying the percentage of attendance and activity of the library, Point is used to encourage library to often answer questions and motivate library to come to the library to borrow books for a longer time by exchange points earned, and utilization of E-books also helps the development of digital library services. Layanan tersebut dapat diakses kapan saja tanpa terbatas ruang maupun waktu sehingga civitas sekolah dapat menggunakannya secara langsung. Selain itu layanan yang ada mendukung perpustakaan dalam menerapkan budaya membaca disekolah. Elemen-elemen gamification yang digunakan yaitu Point, Leaderboard, Challenges & Quests. Berdasarkan hasil uji coba, 46,9% jawaban siswa aplikasi ini sangat menarik, 40,6% aplikasi ini menarik, dan 12,5% aplikasi ini cukup menarik dan 50% jawaban pustakawan aplikasi ini sangat membantu dan 50% aplikasi ini membantu.layanan ini dapat membantu dan mempermudah pemustaka maupun pustakawan dalam melakukan proses membaca maupun pengelolaan data dan laporan.